2017
DOI: 10.1002/adfm.201702695
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Graphitic Carbon Nitride Nanostructures: Synthesis, Modification, and Sensing Applications

Abstract: donating-driven property (e.g., catalysis and strong affinity to Lewis acid). These unique properties motivated huge activity in sensing applications of g-CN, indicating by the growing collection of publications concerning g-CN-based sensors, as displayed in Figure 3.This article reviews state-of-the-art sensing applications of nanostructured g-CN. We begin with a highlight of the diverse micro/nanostructures and nanocomposites of g-CN that are suitable for sensing applications and summarize the known signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(84 citation statements)
references
References 128 publications
(226 reference statements)
0
82
0
1
Order By: Relevance
“…In the past decade, diverse coreactants have been developed mainly including ammonia gas, [8] biomolecules such as 2-(dibutylamino)ethanol and Lcysteine, [9][10][11] and nanomaterials like carbon nanodots and boron nitride quantum dots. [21][22][23][24] Among various nanostructures, g-CN nanosheets (CNNS) with anisotropic two-dimensional geometric morphology exhibit unique features, such as a highly opened-up flat structure with an enlarged surface area, reduced thickness with intrinsic semiconductive property but enhanced electron mobility, and well film-forming capability. [17][18][19] Graphitic carbon nitride (g-CN) is a semiconductor polymer with layer structure whereby intralayer is composed of triazine or tri-s-triazine units connected aromatic planes and interlayer is assembled by Van der Waals force and hydrogen bond.…”
Section: Graphitic Carbon Nitride Nanosheets As Co-reactants For Trismentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, diverse coreactants have been developed mainly including ammonia gas, [8] biomolecules such as 2-(dibutylamino)ethanol and Lcysteine, [9][10][11] and nanomaterials like carbon nanodots and boron nitride quantum dots. [21][22][23][24] Among various nanostructures, g-CN nanosheets (CNNS) with anisotropic two-dimensional geometric morphology exhibit unique features, such as a highly opened-up flat structure with an enlarged surface area, reduced thickness with intrinsic semiconductive property but enhanced electron mobility, and well film-forming capability. [17][18][19] Graphitic carbon nitride (g-CN) is a semiconductor polymer with layer structure whereby intralayer is composed of triazine or tri-s-triazine units connected aromatic planes and interlayer is assembled by Van der Waals force and hydrogen bond.…”
Section: Graphitic Carbon Nitride Nanosheets As Co-reactants For Trismentioning
confidence: 99%
“…[6] Ru(bpy) 3 2 + ECL occurs by means of two pathways: ion annihilation and co-reactant. [21][22][23][24] Among various nanostructures, g-CN nanosheets (CNNS) with anisotropic two-dimensional geometric morphology exhibit unique features, such as a highly opened-up flat structure with an enlarged surface area, reduced thickness with intrinsic semiconductive property but enhanced electron mobility, and well film-forming capability. Ru(bpy) 3 2 + /tripropylamine (TrPA) co-reactant system is currently the most widely used Ru(bpy) 3 2 + ECL system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Graphitic carbon nitride (g-CN) nanomaterials are layered structural semiconductor polymers with triazine or tri-s-triazine units connected aromatic plane in each layer and inherent primary and tertiary amine groups on the surface. [43][44][45][46][47][48] Recently, our group studied ECL responses of Ru(bpy) 3 2 + at glassy carbon electrode (GCE) modified with and without graphitic carbon nitride nanosheets (CNNS), and found that not only the inherent amine groups on the surface of CNNS but also the electrochemically generated charge carriers in CNNS involved in anodic Ru(bpy) 3 2 + ECL. [32] As shown in Figure 4, the Ru(bpy) 3 2 + / CNNS co-reactant ECL occurs by i) the "oxidative-reduction" pathway where Ru(bpy) 3 2 + * is generated via the interaction between Ru(bpy) 3 3 + and the chemical/electrochemical oxidation product of the amine groups on the CNNS surface, and ii) the "reductive-reduction" pathway where Ru(bpy) 3 2 + * is generated via the chemical reaction between Ru(bpy) 3 3 + and the electroreduction product of CNNS.…”
Section: Carbon and Nitride Nanomaterialsmentioning
confidence: 99%
“…Two‐dimensional (2D) carbon nitride (CN) based semiconductors possess great promise in various fields as solar fuels production, bio‐imaging, sensing, light‐emitting diodes and solar cells due to their unique electronic, optical, and structural properties, as well as to their low price, environmentally friendly nature, and high stability to oxidation and harsh chemical condition . The synthesis of CN frameworks usually relies on the condensation of nitrogen‐rich organic molecules, such as urea, dicyandiamide, or melamine, at elevated temperatures .…”
Section: Figurementioning
confidence: 99%